USULAN KEBIJAKAN PEMERIKSAAN PADA GARDU TRAKSI LRT PALEMBANG BERDASARKAN ANALISIS NILAI KEANDALAN DAN KETERSEDIAAN - Putra, Chandra Dwi; Virdyawan , Vani; Rachmilda , Tri Desmana; Suweca, I Wayan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The Palembang LRT, the first light rail transportation system in Indonesia, operates at the traction substation. This research aims to propose an optimal inspection policy based on reliability and availability values. The study found that the reliability of the 750 V output DC cubicle sub-equipment is 84.01%, the feeder is 97.22%, the MV switchgear 20 kV AC is 98.60%, and the power supply controller (SCADA) is 94.04%. The availability value of the 750 V output DC cubicle sub-equipment is 99.99%, the feeder is 99.98%, the MV switchgear 20 kV AC is 99.99%, and the SCADA is 99.97%. The inspection time interval with a reliability target of 90% for the 750 V output DC cubicle sub-equipment is 181 hours, with the feeder sub-equipment having intervals of 1256 hours, MV switchgear 20 kV AC sub-equipment every 2513 hours, and the SCADA sub-equipment every 599 hours.